2016
DOI: 10.1080/03014460.2016.1213313
|View full text |Cite
|
Sign up to set email alerts
|

The timing of mandibular tooth formation in two African groups

Abstract: Background: Ethnic differences in the timing of human tooth development are unclear. Aim: To describe similarities and differences in the timing of tooth formation in two groups of Sudanese children and young adults. Subjects and methods: The sample consisted of healthy individuals from Khartoum, Sudan, aged 2-23 years. The Northern group was of Arab origin (848 males, 802 females) and the Western group was of African origin (846 males, 402 females). Each mandibular left permanent tooth from first incisor to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
2
9
2
Order By: Relevance
“…The second study hypothesis was that dental age predictions in a Somali population behave similarly to comparable age predictions in other studied populations. An abundant number of age estimation outcomes in Black populations have been reported and discussed in the literature [ 12 , 20 , 33 , 35 , 40 , 41 , 43 46 , 48 50 , 59 – 63 ], but they are not comparable with the present study due to differences in study set-ups, sampling, variation in age distribution, teeth considered, age predictors used and staging techniques and age estimation methods applied. Models combining PT + TM have been validated in United Arab Emirati, Brazilian, Japanese and Malaysian children and sub-adults [ 27 30 ].…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The second study hypothesis was that dental age predictions in a Somali population behave similarly to comparable age predictions in other studied populations. An abundant number of age estimation outcomes in Black populations have been reported and discussed in the literature [ 12 , 20 , 33 , 35 , 40 , 41 , 43 46 , 48 50 , 59 – 63 ], but they are not comparable with the present study due to differences in study set-ups, sampling, variation in age distribution, teeth considered, age predictors used and staging techniques and age estimation methods applied. Models combining PT + TM have been validated in United Arab Emirati, Brazilian, Japanese and Malaysian children and sub-adults [ 27 30 ].…”
Section: Discussioncontrasting
confidence: 58%
“…In the literature, controversies still exist regarding possible differences in the dental development between Black and other populations [ 12 , 40 42 ], although more and more evidence of equality has been appearing [ 11 , 20 , 33 , 35 , 43 46 ]. Studies on the dental development in sub-Saharan populations and in Somalis, indigenous to Northeast Africa, are few, however [ 12 , 41 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall MAE when using the Willems BC method is about 22 days larger compared to the Finland, France, South Korea and Sweden not to show major differences [39], apparently also not within two ethnic groups from Sudan. [40] The timing of dental development in children of subsaharan descent has not been studied at large. Some reports were based on datasets of all permanent teeth either including or excluding third molars or on third molars only.…”
Section: / 20mentioning
confidence: 99%
“…The subsequent underestimation of chronological age, which we ascribe to differences in environment, might on the other hand be suggested as being due to genetically based population differences in tooth size and development. While this is a possibility, existing research indicates that observed differences between populations are primarily the result of environmental factors (Cardoso, 2009), with comparisons of samples from diverse geographic origins finding no significant differences in the timing of tooth formation (Elamin, Hector, & Liversidge, 2016; Liversidge, 2003; Liversidge, Speechly, and Hector, 1999; Maber, Liversidge, and Hector, 2006). Of the scarce studies that have examined population variation in tooth length specifically, one found only two teeth differed in size between geographically diverse samples (Smith, Wax, and Adler, 1989), while an analysis of chronologically diverse samples determined only the root length of one tooth differed (Smith et al, 1986).…”
Section: Discussionmentioning
confidence: 99%